2023
DOI: 10.5114/ppn.2023.126482
|View full text |Cite
|
Sign up to set email alerts
|

Family history of stroke – a useful clue for the primary care physician and stroke neurologist: a narrative review

Abstract: Purpose:The heritability of ischemic stroke is a complex mechanism, involving the contribution of genetic traits and environmental factors, which is why in everyday practice clinicians often rely on the broad term "family history of stroke", defined as the case of any first-degree relative who has had a stroke. The aim of this review is to update the available data regarding family history of stroke in primary and secondary stroke prevention by searching the electronic Scopus database for the phrase TITLE-ABS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 138 publications
0
1
0
Order By: Relevance
“…In patients with good collateral circulation, once blood vessels are occluded and thrombosis is formed, collateral vessels will provide part of the blood supply, leading to slow brain tissue ischemia, less necrosis of brain cells, and relatively mild neurological function defect. In addition, studies have shown that a family history of stroke is an important risk factor for obesity and hyperlipidemia ( 48 , 49 ), and these patients may also have cardiovascular and metabolic diseases. They will have active health improvement behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with good collateral circulation, once blood vessels are occluded and thrombosis is formed, collateral vessels will provide part of the blood supply, leading to slow brain tissue ischemia, less necrosis of brain cells, and relatively mild neurological function defect. In addition, studies have shown that a family history of stroke is an important risk factor for obesity and hyperlipidemia ( 48 , 49 ), and these patients may also have cardiovascular and metabolic diseases. They will have active health improvement behaviors.…”
Section: Discussionmentioning
confidence: 99%